(untitled) (Ukrainian Journal of Ophthalmology, 2023)
This review discusses the experience in applying laser flare photometry, a non-invasive technique, in ophthalmology, to assess quantitatively the state of the blood-aqueous barrier (BAB) in patients with certain ocular and systemic disorders. The method allows reliable detection of such biomarkers of the state of the BAB as the intensity of the scattered light (flare) and number of cells in the aqueous of the anterior chamber, sometimes even at the subclinical level, which significantly improves the capability for early diagnosis and objective treatment monitoring.